Oleochemical synthesis of sulfanes, their structure and properties - Bodachivskyi, Iurii; Pop, Grigoriy; Zheleznyi, Leonid; Zubenko, Stepan; Okhrimenko, Mykhailo (Lviv Politechnic Publishing House, 2017)
Вперше внаслідок послідовної вулканізації алкілових естерів вищих жирних кислот ріпакової олії пероксидом бензоїлу та елементним сульфуром синтезовано олеохімічні сульфани. Методами інструментального аналізу встановлено їх будову і властивості. Показано, що олеохімічні сульфани – комлексні структури різного ступеню зшивання, характеризуються відмінними антиокиснювальними й трибо- логічними властивостями і не викликають корозії міді та сталі зажорстких умов тестування.

For the first time, oleochemical sulfanes were synthesized via sequential vulcanization of fatty acid alkyl esters from rapeseed oil by benzoyl peroxide and elemental sulfur. Their structure and properties were established by the methods of instrumental analysis and it was shown that oleochemical sulfanes are complex structures with different cross-linking degrees, which provide excellent antioxidant and tribological characteristics and do not cause steel or copper corrosion under harsh test conditions.
Олеохімічний синтез сульфанів, їх будова та властивості
Keywords: ріпакова олія; органічні сульфани; синтез; механізми реакцій; додатки до мастильних матеріалів; rapeseed oil; organic sulfanes; synthesis; reaction mechanisms; lubricant additives